2014
DOI: 10.3844/ajassp.2014.96.104
|View full text |Cite
|
Sign up to set email alerts
|

Role of Work-Family Enrichment in Improving Job Satisfaction

Abstract: The role of work-family enrichment in improving job satisfaction has been given little attention. In this study a mediation model was tested which includes work-family enrichment as the mediator, job characteristics (job autonomy and job involvement) as antecedent factors and job satisfaction as the outcome. Data were gathered from 280 public secondary school teachers in Malaysia using selfadministered questionnaires. Work-family enrichment partially mediated the relationships between job characteristics and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
3
11
0
Order By: Relevance
“…Carlson, Grzywacz and Kacmar (2010) noted that work-to-family enrichment was strongly correlated with job satisfaction, suggesting that when workers recognise the benefits families receive from their work, they attribute those synergies to the source, which, in turn, benefits job satisfaction. Fung, Ahmad and Omar (2014) also confirmed a significantly strong relationship between work-family enrichment and job satisfaction. With the inclusion of productivity (job satisfaction in the alternative model) in the second step as predictor of job satisfaction (productivity in the alternative model), the variance explained in job satisfaction (productivity in the alternative model) significantly increased, suggesting that not only may employees who are happy with their jobs be more productive, but performing a job well may lead to satisfaction with the job (Judge & Klinger 2009).…”
Section: Discussionsupporting
confidence: 55%
“…Carlson, Grzywacz and Kacmar (2010) noted that work-to-family enrichment was strongly correlated with job satisfaction, suggesting that when workers recognise the benefits families receive from their work, they attribute those synergies to the source, which, in turn, benefits job satisfaction. Fung, Ahmad and Omar (2014) also confirmed a significantly strong relationship between work-family enrichment and job satisfaction. With the inclusion of productivity (job satisfaction in the alternative model) in the second step as predictor of job satisfaction (productivity in the alternative model), the variance explained in job satisfaction (productivity in the alternative model) significantly increased, suggesting that not only may employees who are happy with their jobs be more productive, but performing a job well may lead to satisfaction with the job (Judge & Klinger 2009).…”
Section: Discussionsupporting
confidence: 55%
“…Research results showed that WFE has a positive effect on job satisfaction. The results of this study support previous research conducted by Akram et al (2014), Carlson et al (2010), Carlson (2014), Fung et al (2014), Michel (2015), McNall et al (2010a), and Tang et al (2014), who found that WFE was positively related to job satisfaction. This finding supports the originating domain view theory which states that the domain from which enrichment originates is the domain that gets the main benefit.…”
Section: Discussionsupporting
confidence: 91%
“…Akram et al (2014) found that WFE is a significant predictor of job satisfaction, and Carlson et al (2010) found that WFE has positive relationship with job satisfaction. Fung et al (2014) pointed out that WFE implies positive relationship with job satisfaction. Michel and Michel (2015) showed that WFE implies positive and significant relationship with job satisfaction.…”
Section: Wfe and Job Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations